2016
DOI: 10.1038/srep32246
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon regulates hepatic lipid metabolism via cAMP and Insig-2 signaling: implication for the pathogenesis of hypertriglyceridemia and hepatic steatosis

Abstract: Insulin induced gene-2 (Insig-2) is an ER-resident protein that inhibits the activation of sterol regulatory element-binding proteins (SREBPs). However, cellular factors that regulate Insig-2 expression have not yet been identified. Here we reported that cyclic AMP-responsive element-binding protein H (CREBH) positively regulates mRNA and protein expression of a liver specific isoform of Insig-2, Insig-2a, which in turn hinders SREBP-1c activation and inhibits hepatic de novo lipogenesis. CREBH binds to the ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 42 publications
1
33
0
Order By: Relevance
“…Activated CREB also stimulates expression of the nuclear hormone receptor coactivator known as peroxisome proliferator-activated receptor gamma co-activator 1-alpha (PGC-1α), which upregulates gluconeogenic genes as well as genes involved in mitochondrial fatty acid oxidation [54]. Additionally, a recent study reported that CREB can also regulate the activity of sterol regulatory element-binding protein-1c (SREBP-1c), a transcription factor for lipogenic genes involved in de novo hepatic lipogenesis, such as fatty acid synthase, through the insulin induced gene-2 (Insig-2) [55]. The outcomes of PKA activation in the liver are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Activated CREB also stimulates expression of the nuclear hormone receptor coactivator known as peroxisome proliferator-activated receptor gamma co-activator 1-alpha (PGC-1α), which upregulates gluconeogenic genes as well as genes involved in mitochondrial fatty acid oxidation [54]. Additionally, a recent study reported that CREB can also regulate the activity of sterol regulatory element-binding protein-1c (SREBP-1c), a transcription factor for lipogenic genes involved in de novo hepatic lipogenesis, such as fatty acid synthase, through the insulin induced gene-2 (Insig-2) [55]. The outcomes of PKA activation in the liver are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1) (Stark and Keller 1987, Cordoba-Chacon et al 2015, Wang et al 2016a. Growth hormone deficiency in NAFLD may contribute to hepatic steatosis by removing GH-mediated suppression of DNL.…”
Section: De Novo Lipogenesismentioning
confidence: 99%
“…Plasmas and livers were collected 10h after LPS treatment for further analysis. Tissue collections were performed at the end points of each experiment, as follows: animals were anesthetized using isoflurane (3% mixed with oxygen), tissues were excised and flash frozen in liquid nitrogen, and livers were then homogenized in solubilization buffer for further analysis as described previously [24, 25]. …”
Section: Methodsmentioning
confidence: 99%